Effects of Skin Thickness on Cochlear Input Signal Using Transcutaneous Bone Conduction Implants. Issue 8 (September 2015) - Mattingly, Jameson K.; Greene, Nathaniel T.; Jenkins, Herman A.; Tollin, Daniel J.; Easter, James R.; Cass, Stephen P.
<x xml:space="preserve">Abstract</x> Hypothesis Intracochlear sound pressures (PIC) and velocity measurements of the stapes, round window, and promontory (VStap/RW/Prom) will show frequency-dependent attenuation using magnet-based transcutaneous bone conduction implants (TCBCIs) in comparison with direct-connect skin-penetrating implants (DCBCIs). Background TCBCIs have recently been introduced as alternatives to DCBCIs. Clinical studies have demonstrated elevated high-frequency thresholds for TCBCIs as compared with DCBCIs; however, little data exist examining the direct effect of skin thickness on the cochlear input signal using TCBCIs. Methods Using seven cadaveric heads, PIC was measured in the scala vestibuli and tympani with fiber-optic pressure sensors concurrently with VStap/RW/Prom via laser Doppler vibrometry. Ipsilateral titanium implant fixtures were placed and connected to either a DCBCI or a TCBCI. Soft tissue flaps with varying thicknesses (no flap and 3, 6, and 9 mm) were placed successively between the magnetic plate and sound processor magnet. A bone conduction transducer coupled to custom software provided pure-tone stimuli between 120 and 10, 240 Hz. Results Stimulation via the DCBCI produced the largest response magnitudes. The TCBCI showed similar PSV/ST and VStap/RW/Prom with no intervening flap and a frequency-dependent nonlinear reduction of magnitude with increasing flap thickness. Phase shows a comparable dependence on transmission delay as the acoustic baseline, and the slope steepens at higher frequencies as flap thickness increases, suggesting a longer group delay. Conclusion Proper soft tissue management is critical to optimize the cochlear input signal. The skin thickness–related effects on cochlear response magnitudes should be taken into account when selecting patients for a TCBCI.